Fin-de-Siècle Fictions, 1890s-1990s Apocalypse, Technoscience, Empire - Mousoutzanis, A.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Fin-de-Siècle Fictions, 1890s- 1990s focuses on fin-de-siècle British and postmodern American fictions of apocalypse and investigates the ways in which these narratives demonstrate shifts in the relations among modern discourses of power and knowledge.
Keywords: Literature, Modern—20th century; British literature; Literature—Philosophy.; Fiction; Literature, Modern—19th century; America—Literatures.; Twentieth-Century Literature; British and Irish Literature; Literary Theory; Fiction; Nineteenth-Century Literature; North American Literature